Electrolyte design for reversible zinc metal chemistry - Bao Zhang; Jia Yao; Chao Wu; Yuanjian Li; Jia Liu; Jiaqi Wang; Tao Xiao; Tao Zhang; Daqian Cai; Jiawen Wu; Zhi Wei Seh; Shibo Xi; et al. (Nature Communications)
Abstract Metal anodes hold significant promise for next-generation energy storage, yet achieving highly reversible plating/stripping remains challenging due to dendrite formation and side reactions. Here we present a tailored electrolyte design to surpass 99.9% Coulombic efficiency (CE) in zinc metal anodes by co-engineering salts and solvents to address two critical factors: plating morphology and the anode-electrolyte interface. By integrating a dual-salt approach and organic co-solvent design, these issues can be effectively addressed. The resulting hybrid dual-salt electrolyte renders CE of 99.95% at 1 mA cm−2 at a medium concentration (3.5 m). Building upon the near-unity CE, an anode-free cell with ZnI2 cathode can stably run more than 1000 cycles under practical conditions with minimal capacity loss. Our findings provide a promising pathway for the design of reversible metal anodes, advancing metal-based battery technologies for broader energy storage applications.